2012
DOI: 10.1007/s11789-012-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic apheresis in peripheral and retinal circulatory disorders

Abstract: In microcirculation disorders, the therapeutic apheresis seems to have two different effects. The first, achieved after only a few sessions, is acute, consisting of drastic reduction of blood viscosity and obtained with the use of low-density lipoprotein (LDL) apheresis, rheopheresis, or fibrinogen apheresis. The second effect is long term, or chronic, and needs to be evaluated after a long course of treatment. The mechanisms underlying the chronic effect are still objects of debate and take into account the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In a previous study, we found that patients with pAMR had significant and sustained reductions in fibrinogen levels when compared to other patient populations who receive daily TPE . Although fibrinogen only accounts for approximately 4% of plasma proteins, its concentration is the major determinant of plasma viscosity and blood rheology owing to its large size . Using 5% albumin as the replacement fluid during TPE causes a rapid reduction in blood viscosity and resistance to blood flow through vessels due to depletion of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we found that patients with pAMR had significant and sustained reductions in fibrinogen levels when compared to other patient populations who receive daily TPE . Although fibrinogen only accounts for approximately 4% of plasma proteins, its concentration is the major determinant of plasma viscosity and blood rheology owing to its large size . Using 5% albumin as the replacement fluid during TPE causes a rapid reduction in blood viscosity and resistance to blood flow through vessels due to depletion of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Using 5% albumin as the replacement fluid during TPE causes a rapid reduction in blood viscosity and resistance to blood flow through vessels due to depletion of fibrinogen. In certain disorders of the microcirculation (e.g., sudden hearing loss, nonarteritic anterior ischemic optic neuropathy, and peripheral arterial disease), reducing blood viscosity by removing fibrinogen results in rapid resolution of the disorder, usually following 1 or 2 treatments . We speculated that the rapid improvement of cardiac allograft function following TPE may be due to changes in the rheologic properties of blood as acute reductions in fibrinogen and viscosity following TPE may improve perfusion of the allograft and increase cardiac contractility.…”
Section: Discussionmentioning
confidence: 99%
“…RHF is used for the treatment of sudden hearing loss, age-related macular degeneration, peripheral arterial disease, and several other microcirculatory diseases [ 6 , 7 , 12 , 13 ]. Data supporting the efficacy of this procedure have been published, but detailed pathophysiological explanations of the positive clinical effects are not clear or are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorheology is determined by the viscosity of the plasma/whole blood as well as the erythrocyte deformability and tendency to aggregate. 1…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in the mircocirculatory parameters might correct, at least partially, the functional properties of the anatomic entity affected, that is, an improvement in the ischemic symptoms of PAD, or a partial correction/stabilization of visual acuity in patients with AMD. 1…”
Section: Introductionmentioning
confidence: 99%